The effect of salary Domiciliation in the rate of return on assets (ROA): Applied research of a sample of Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Abstract The research attempted to find an explanation and solution to a problem related to the fluctuation and decrease In the rate of return on assets for the research sample banks during the duration of the research, The search started from the hypothesis that, The effect of salary Domiciliation on the banking profitability of a sample of Iraqi banks participating in the salary settlement system for the period (2016-2019),The research used the descriptive historical approach, the quantitative analytical approach and the statistical approach. The research reached a set of conclusions, the most important of which is The effect of salary Domiciliation on banking profitability was achieved in three banks at a rate of (50%) of the sample banks. The research also recommended a set of proposals, the most important of which was, The necessity of taking into consideration the Central Bank of Iraq as the sponsor of the salary settlement system, Induce the Iraqi banks participating in it, to expand the range of services provided In light of the electronic payment service for salaries and wages, and searching for services provided by international banks that fall within the scope of electronic payment, and providing them to the public in the Iraqi environment, and in this field the research provides a set of services already applied to international banks, which the Iraqi banking sector lacks, such as a service Masterbase, (Social Pay), application service (online platform) that includes a range of services such as automatic saving and providing financial advice to clients, The necessity of The Central Bank of Iraq to reconsider the commissions cut from the process of transferring the salary to the beneficiary, by reducing those commissions, as over time the beneficiaries of this service will increase, and this increase leads to a reduction in the costs of that system to the participating banks, as a result of distributing them to the largest possible number, which The sponsor of this system is obliged to reduce these commissions.